Sistem Pendukung Keputusan Pemilihan Pakaian Menggunakan Metode Topsis - Nikmah, Siti Mauidhotun; Zayn , Afta Ramadhan; Rohmah, Roihatur (Al-Mantiq, 2025)
This research implements a Decision Support System (DSS) using the TOPSIS method to determine clothing quality at Najah Fashion Store. The study aims to assist consumers, especially teenagers, in selecting quality clothing that meets their needs and budget. The TOPSIS method is applied through stages of determining criteria, alternatives, attributes, and weights. The system focuses on two clothing categories: gamis (long dresses) and shirts, with criteria including material, price, and color. Results show that the system successfully recommends a gamis made of zira ceruty fabric (code A02) with an alternative value of 0.716 and a postilo shirt (code C1) with a value of 0.662. Calculations were performed both manually and through the application, with consistent results. Blackbox testing demonstrated 100% validity of system functions. In conclusion, the developed DSS effectively aids Najah Fashion Store in sales and facilitates consumers in choosing the best clothing based on desired criteria.